The influential product manager : how to lead and launch successful technology products - Sandy, Ken (Berrett-Koehler Publishers, 2020)
From setting priorities to capturing requirements to navigating trade-offs, this comprehensive book methodically documents the tools product managers everywhere use to align their teams with market needs and organizational goals. --